Practical Pediatric Cardiology Case-Based Management of Potential Pitfalls - Magee, Alan G.; Till, Jan; Seale, Anna N. (Springer London : Imprint: Springer, 2016)
This book is a collection of cases highlighting situations which can ensnare even the best cardiologist working with pediatric patients. Heart disease in children has a number of diagnostic traps for the unwary, and many of those involved in the specialty have been caught at one time or another. Although the cases contained within these pages illustrate the importance of taking a good history and performing a thorough examination, the most important lesson is learning to keep an open mind and develop the ability to think laterally. For example, it is sometimes very difficult to differentiate between respiratory and cardiac disease in infants and between neurological and cardiac conditions in older children, and the consequences of taking the wrong path can be significant. Practical Pediatric Cardiology is made up of concise chapters that are designed to shed some light on the often difficult management decisions in this group of patients. The chapters represent a wide range of clinical experience and thus will be useful for all readers from those in training through nursing and emergency medical professionals to practicing pediatric cardiologists and cardiac surgeons.